Early Islamic Educational Institutions in Islamic Educational Science - Esmat, Lamis Ahmad; Nurhakim; Faridi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Education during the era of the Messenger, may God’s prayers and peace be upon him, was completely similar to what exists in our current era. The only difference was in the names, but the institutions during the era of the Messenger had the same characteristics and the same tasks, as well as the same scientific approaches followed, and perhaps the Prophet’s approach was better, Since he enjoyed plurality and diversity, and also the method of the Messenger did not follow the external control, but rather the internal control, so each of the Muslims was observing himself in order to perform the best that he had, and therefore it was distinguished by simplicity in the beginning due to the modernity of the era, and then it was characterized by progress in the civil era.. The research method used is literature with documentation data collection techniques. The results of this research are summarized in the fact that during the Meccan period there was one institution based on the education of Muslims, but it was teaching them only the matters of their religion, and this is due to the difficulty of life for Muslims at the time. The difference between both of them, and the characteristics that distinguished each era from them, who were its founders, and the methods used at that time.